Anuran captured in pitfall traps in three agrossystem in Northwestern São Paulo State, Brazil - Silva, Fernando Rodrigues da [UNESP]; Santos, Rodrigo Souza; Nunes, Maria Andréia [UNESP]; Rossa-Feres, Denise de Cerqueira [UNESP] (Instituto Virtual da Biodiversidade (BIOTA/FAPESP), 2009)
Embora seja geralmente assumido que a agricultura influencia negativamente populações de anfíbios, existem poucos estudos sobre os efeitos dos cultivos agrícolas em anuros neotropicais. Visando contribuir para diminuir essa lacuna de conhecimento, no presente estudo buscamos verificar quais espécies de anuros estão presentes nos agrossistemas. Para isso, usamos dados de anuros capturados em armadilhas de queda, inicialmente proposto para o levantamento da fauna de opiliões em três agrossistemas (milho, soja e seringal). Nós registramos quatro espécies de anuros nas armadilhas de queda: Leptodactulus fuscus, L. mystacinus (Leptodactylidae), Eupemphix nattereri e Physalaemus cuvieri (Leiuperidae). Na plantação de milho foram registradas quatro espécies e 30 indivíduos, no seringal quatro espécies e 11 indivíduos e na plantação de soja três espécies e oito indivíduos. Nossos resultados mostram que os anuros estão presentes nos agrossistemas, principalmente espécies de anuros generalistas.

Although it is generally assumed that agriculture negatively influences amphibian populations, few studies on the effects of agricultural cultivations on neotropical anuran have been conducted. As a contribution to the knowledge about anuran in agriculture, the present study sought to identify the anuran species present in three different agrossystems. We used data from anurans captured in pitfall traps initially proposed for a survey of harvestmen fauna in three agrossystems (corn, soybean, and rubber tree). Four anuran species found in the pitfall traps belong to two Families: Leptodactylidae: Leptodactulus fuscus and L. mystacinus; and Leiuperidae: Eupemphix nattereri and Physalaemus cuvieri. In corn plantation, four species and 30 individuals were captured; in rubber trees, four species and 11 individuals; and in soybeans plantation, tree species and eight individuals. Our results show that anurans are present in agrossystems, mainly the generalist anuran species.
Anuros capturados em armadilhas de queda em três agrossistemas no noroeste paulista, Brasil
Keywords: anfíbios; plantação de soja; plantação de milho e seringal; Amphibian; soybean plantation; corn plantation and rubber tree